Universal student enrollment systems: The more policies change, the more enrollment patterns stay the same - Lauren Sartain; Riley Lewers; Lisa Barrow (Federal Reserve Bank of Chicago, 2022)
Urban school districts nationwide have increased within-district choice for families. In response, district policymakers are overhauling the systems for applying to and enrolling in schools, with the goal of making it easier and more equitable for students to enroll in schools that are a good fit for them. These universal enrollment systems offer a one-stop shop for students to learn about different options, submit applications, and receive and accept offers. Using the implementation of such a system in Chicago Public Schools, we examine how applications to, offers from, and enrollment in different types of high schools (e.g., high-performing vs. low-performing schools, charter vs. neighborhood schools) changed. The largest gains appear to be from streamlining applications and offers, with students receiving a single-best offer and schools having more certainty around their incoming ninth-grade class. We do not see changes in the shares of students enrolled at high schools with high graduation rates or at charter schools that can be attributed to the new system. These findings suggest that while universal enrollment systems can improve and simplify the application process, they are not a panacea for inequitable access to attending high-performing schools.
Keywords: I20; I21; I24; I28; 330; School Choice; Student Enrollment; School Quality; High Schools